Estimation of deposit and spray distribution in hydro sensible paper and morning glory plant - Maciel, Cleber Daniel de Goes; Velini, Edivaldo Domingues [UNESP]; Souza, Reginaldo Teodoro de; Souza, João Igor de; Chagas, Rafael Ravaneli; Silva, Marco Antonio Santos; Poletine, Juliana Parisotto (My University, 2014)
Herbicides application success depends, besides product correct choice, the observation of environmental conditions and application quality. The work aimed to quantify the effects of surfactant addition in spraying solution, in natural and artificial targets, associated to different nozzle boom angles in relation to application offset, by using distinct evaluation methods. Two experiments were conducted at NuPAM-FCA/UNESP, Botucatu County, São Paulo State, constituted by ten treatments, in factorial scheme 2 × 5, corresponding to two spraying solutions conditions (absence or presence of Aterbane BRTM (0.25% v/v) adjuvant) and five angles of spray nozzle in relation to offset application (-30°, -15°, 90°, +15° and +30°). In Ipomea grandifolia leaves, the distribution and drops deposition of a tracer solution were evaluated by using scores visual and spectrophotometer process. In hydro sensible papers, volumetric medium diameter (VMD), density (cm2 ) and drops medium diameter, covered area (%) and application fees (L ha-1) were evaluated through e-SprinkleTM software. Aterbane BRTM (0.25% v/v) presence or absence, associated or no, to spray nozzles offset did not provide significant differences in I. grandifolia spray deposition. The use of artificial targets presented applicative technical limitations in relation to the use of natural ones as study matrix. Deposit and distribution variables esteem distinct behaviours, independent of target nature.
Keywords: Target; Tracer; Deposition; Application technology